Cancer Cell Gene Expression Modulated from Plasma Membrane Integrin αvβ3 by Thyroid Hormone and Nanoparticulate Tetrac - Davis, Paul J.; Glinsky, Gennadi V.; Lin, Hung-Yun; Leith, John T.; Hercbergs, Aleck; Tang, Heng-Yuan; Ashur-Fabian, Osnat; Incerpi, Sandra; Mousa, Shaker A. (Frontiers in Endocrinology, 2015)
Integrin αvβ3 is generously expressed by cancer cells and rapidly dividing endothelial cells. The principal ligands of the integrin are extracellular matrix proteins, but we have described a cell surface small molecule receptor on αvβ3 that specifically binds thyroid hormone and thyroid hormone analogues. From this receptor, thyroid hormone (L-thyroxine, T4; 3,5,3’-triiodo-L-thyronine, T3) and tetraiodothyroacetic acid (tetrac) regulate expression of specific genes by a mechanism that is initiated nongenomically. At the integrin, T4 and T3 at physiological concentrations are pro-angiogenic by multiple mechanisms that include gene expression, and T4 supports tumor cell proliferation. Tetrac blocks the transcriptional activities directed by T4 and T3 at αvβ3, but, independently of T4 and T3, tetrac modulates transcription of cancer cell genes that are important to cell survival pathways, control of the cell cycle, angiogenesis, apoptosis, cell export of chemotherapeutic agents and repair of double-strand DNA breaks. We have covalently bound tetrac to a 200 nm biodegradable nanoparticle that prohibits cell entry of tetrac and limits its action to the hormone receptor on the extracellular domain of plasma membrane αvβ3. This reformulation has greater potency than unmodified tetrac at the integrin and affects a broader range of cancer-relevant genes. In addition to these actions on intracellular kinase-mediated regulation of gene expression, hormone analogues at αvβ3 have additional effects on intracellular protein-trafficking (cytosol compartment to nucleus), nucleoprotein phosphorylation and generation of nuclear coactivator complexes that are relevant to traditional genomic actions of T3. Thus, previously unrecognized cell surface-initiated actions of thyroid hormone and tetrac formulations at αvβ3 offer opportunities to regulate angiogenesis and multiple aspects of cancer cell behavior.